2008
DOI: 10.1071/sb08034
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic revision of Australasian snow hebes (Veronica, Plantaginaceae)

Abstract: The snow hebes, formerly comprising the genus Chionohebe, are here included within Veronica (Plantaginaceae). The five species (including two subspecies) of snow hebes recognised here are cushions or subshrubs that occur exclusively in high-elevation habitats of Australia and the South Island of New Zealand. Species delimitation among the cushion snow hebes is very difficult because of the reduced pulvinate habit, solitary flowers and few gross-morphological characters useful for identification. To address spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Recent molecular phylogenetic studies have shown that several previously separate New Zealand genera are included within Veronica , whereby the following informal names were proposed for these subclades within section Hebe (Fig. 1; Wagstaff and Garnock‐Jones, 1998; Albach and Meudt, 2010): the core hebes (originally genus Hebe , 88 species sensu Bayly and Kellow, 2006) that range from subshrubs with “whipcord” habit (scale‐like leaves) to small trees; speedwell hebes (previously Parahebe , 13 New Zealand species and 11 from New Guinea not included in this analysis, Garnock‐Jones and Lloyd, 2004), herbs or subshrubs closer in morphology to the northern hemisphere herbaceous Veronica habit; sun hebes (previously Heliohebe, 5 species, Garnock‐Jones, 1993), decumbent subshrubs; snow hebes (previously Chionohebe and some Parahebe , 10 species; Meudt, 2008; Meudt and Bayly, 2008), alpine cushion plants; and semi‐whipcord hebes (previously Leonohebe, 4 species sensu Bayly and Kellow, 2006), also with a whipcord habit. Past studies based on chloroplast and ribosomal internal transcribed spacer (ITS) markers have achieved high bootstrap support (BS) for monophyly of each subclade with limited phylogenetic resolution within these groups due to lack of variation in the markers (Albach and Meudt, 2010; Meudt et al, 2015).…”
Section: Figurementioning
confidence: 99%
“…Recent molecular phylogenetic studies have shown that several previously separate New Zealand genera are included within Veronica , whereby the following informal names were proposed for these subclades within section Hebe (Fig. 1; Wagstaff and Garnock‐Jones, 1998; Albach and Meudt, 2010): the core hebes (originally genus Hebe , 88 species sensu Bayly and Kellow, 2006) that range from subshrubs with “whipcord” habit (scale‐like leaves) to small trees; speedwell hebes (previously Parahebe , 13 New Zealand species and 11 from New Guinea not included in this analysis, Garnock‐Jones and Lloyd, 2004), herbs or subshrubs closer in morphology to the northern hemisphere herbaceous Veronica habit; sun hebes (previously Heliohebe, 5 species, Garnock‐Jones, 1993), decumbent subshrubs; snow hebes (previously Chionohebe and some Parahebe , 10 species; Meudt, 2008; Meudt and Bayly, 2008), alpine cushion plants; and semi‐whipcord hebes (previously Leonohebe, 4 species sensu Bayly and Kellow, 2006), also with a whipcord habit. Past studies based on chloroplast and ribosomal internal transcribed spacer (ITS) markers have achieved high bootstrap support (BS) for monophyly of each subclade with limited phylogenetic resolution within these groups due to lack of variation in the markers (Albach and Meudt, 2010; Meudt et al, 2015).…”
Section: Figurementioning
confidence: 99%
“…ϩ Chionoside C (8) ϩ Chionoside D (9) ϩ Chionoside E (10) ϩ Chionoside F (11) ϩ Isoaragoside (19) ϩ Isochionoside K (20) ϩ Isochionoside A (21) ϩ Isochionoside B (22) ϩ Ehrenoside (16) ϩ Lagotoside (17) ϩ ϩ Isochionoside J (18) ϩ Persicoside (12) ϩ Chionoside G (13) ϩ Chionoside H (14) ϩ Chionoside I (15) ϩ ϩ Isopersicoside (23) ϩ ϩ ϩ Isochionoside G (24) ϩ Isochionoside H (25) ϩ ϩ Isochionoside I (26) ϩ ϩ ϩ Acylsugars 6Ј-Feruloyl-sucrose (27) ϩ (Table 2) were assigned as above. The 13 C-NMR spectrum showed 42 signals including two of double intensity (d C 127.6, 116.5).…”
Section: Phenylethanoid and Iridoid Glycosides In The New Zealand Snomentioning
confidence: 99%
“…The widely used classification of snow hebes in Flora of New Zealand (as Pygmea) 32) was based on leaf trichomes, which show significant interspecific and intraspecific variations. 18,19) The DNA sequence data and amplified fragment length polymorphism (AFLP) analyses show well-defined lineages within the group. 19) The chemical profile of V. thomsonii is distinct from V. pulvinaris (Table 1).…”
Section: Phenylethanoid and Iridoid Glycosides In The New Zealand Snomentioning
confidence: 99%
See 1 more Smart Citation
“…Albach & Chase (2001), , , Mabberley (2008), Albach (2008) and Albach & Meudt (2010) also presented arguments for including all the southern genera in a wide and monophyletic circumscription of Veronica. Briggs & Ehrendorfer (2006a), Jensen et al (2008), Mabberley (2008), Meudt (2008), Taskova et al (2008Taskova et al ( , 2012, Humphries & Linder (2009), Hughes et al (2010, Pufal et al (2010), Lee et al (2011), Heenan (2012, Lord et al (2013), and the Landcare Research herbarium and databases (see Breitwieser et al 2012) have followed this wider circumscription. Nevertheless, other New Zealand botanists have explicitly rejected an inclusive monophyletic circumscription of Veronica (Gardner 2007;Thorsen 2007;Norton & Molloy 2009;de Lange 2011a;Mark 2012;de Lange et al 2013;Wilson 2013).…”
Section: Lamiaceaementioning
confidence: 99%